Chuckwagon Field Study on 148 Horses: Racing Consecutive Days Affects Baseline Blood Electrolytes, pH and Lactate But Does Not Increase the Prevalence of Cardiac Arrhythmias. (June 2014) - Massie, S; Leguillette, R
Abstract : Introduction: Chuckwagon racing involves 4 Thoroughbred horses pulling a 600 kg wagon through a figure‐8 pattern and running a 1000 m dash. Horses can race four days in a row and there are concerns regarding the contribution of cumulative racing to electrolyte imbalances, arrhythmias, and sudden death, and its impact on recovery. The objective was to investigate the effects of cumulative racing on plasma electrolytes, lactate and prevalence of cardiac arrhythmias. Methods: 148 horses (9.0 ± 2.7 years) from 13 teams were monitored for heart rate and ECG activity on racing days 1 and 2. Differences in plasma electrolytes, pH and lactate (pre‐vs. post‐exercise and between days) were analysed (paired t‐test). Associations between electrolytes and the presence of arrhythmias during racing and recovery (Pearson correlation) were examined. Results: 377 ECGs (82 incomplete due to lost electrode) and 750 plasma samples (374 pre, 376 post) were analysed. 4235 arrhythmic events (21.6% warm‐up, 37.6% racing, 20.4% recovery) were recorded and were not different between days 1 and 2. They mainly comprised supraventricular premature contractions during warm‐up and racing (48% and 81.4% respectively) and ventricular premature contractions during recovery (29.2%). A significant association was found between post‐exercise electrolytes and the presence of arrhythmias during racing (P<0.001, r = 0.17). Consecutive racing significantly increased post‐exercise lactate on day 2 (P<0.001). Pre‐exercise pH and electrolytes were significantly different on day 2. Conclusions: An association exists between post‐exercise electrolytes and occurrence of arrhythmias during consecutive racing, however it is of little clinical significance. Ventricular arrhythmias are as prevalent in chuckwagon horses as in other disciplines. Overall, repetitive racing is well tolerated. Ethical Animal Research: The study was approved by the Veterinary Sciences Animal Care Committee of the University of Calgary (AC120049) and owner informed consent was obtained.Sources of funding:  Clinical Research Fund from the University of Calgary's Faculty of Veterinary Medicine. Summer Studentships were funded by NSERC.Competing interests:  none.